Plant species of the genus Pedicularis L. In the territory of the Western Balkans: Overview of use in traditional medicine, phytochemistry, biological and pharmacological activity - Zubić Nevena G.; Tomović Jovica (Kragujevac Journal of Science)
Modern pharmacotherapy is based on chemical substances derived from plants and herbal medicine from the past. Pedicularis L. is one of the largest genera of hemiparasitic flowering plants, with over 500 species known. It is mostly found in the cold highlands of the northern hemisphere. Numerous endemic Pedicularis species may be found in the Balkans, demonstrating their significance in plant endemism. However, several of these species may face conservation issues due to human activities like habitat fragmentation, agricultural development, and other pressures. Monitoring their numbers, protecting their habitat, and increasing public understanding of their significance are the goals of conservation initiatives. By conducting field surveys and molecular analysis to comprehend their evolutionary relationships, researchers are still working to improve the taxonomic classifications of Balkan Pedicularis species. The chemicals from Pedicularis plant species that have been identified so far have been shown to have anti-tumor, hepatoprotective, immunomodulatory, anti-inflammatory, antidiabetic, antibacterial, antifungal, analgesic, and diuretic properties in research published in the literature. This paper provides an overview of previous research in the Western Balkans.